Echocardiography-Guided Management of Preterms With Patent Ductus Arteriosus Influences the Outcome: A Cohort Study - Terrin, Gianluca; Di Chiara, Maria; Boscarino, Giovanni; Versacci, Paolo; Di Donato, Violante; Giancotti, Antonella; Pacelli, Elisabetta; Faccioli, Francesca; Onestà, Elisa; Corso, Chiara; Ticchiarelli, Alessandra; De Curtis, Mario (Frontiers in Pediatrics, 2020)
Introduction: Echocardiography (ECHO) with color flow Doppler is considered as the gold standard to identify a hemodynamic patent ductus arteriosus (hs-PDA). However, the optimal diagnostic and therapeutic management for newborns with hs-PDA is still controversial. We aimed to investigate two clinical strategies: (1) targeted treatment based on ECHO criteria and (2) treatment based on ECHO criteria in addition to clinical signs and symptoms. Materials and Methods: This is a cohort study including all neonates consecutively admitted in the Neonatal Intensive Care Unit of University La Sapienza in Rome, with gestational age <32 weeks or body birth weight <1,500 g and with a diagnosis of hs-PDA as confirmed by ECHO evaluation performed within 72 h of life. We classified the babies in two cohorts: (A) pharmacological treatment immediately after ECHO screening and (B) pharmacological therapy for PDA was administered when the relevance of a hs-PDA was associated with clinical signs of hemodynamic instability. Results: We considered as primary outcome newborns who survived without any morbidities (A: 48.1% vs. B: 22.2%, p = 0.022). In particular, we found that the rate of intraventricular hemorrhage stage ≥2 was increased in cohort B (A: 3.7% vs. B 24.4%, p = 0.020). A multivariate analysis showed that assignment to cohort A independently influences the primary outcome. Conclusions: Adopting an hs-PDA management option based on ECHO-directed therapy regardless of symptoms may reduce the morbidity and improve the survival of very low birth weight infants.